PERAN ILMU EKONOMI DALAM PEMBERDAYAAN EKONOMI RAKYAT - Mubyarto, Mubyarto (Journal of Indonesian Economy and Business, 2002)
Policy to empower the peopleâs economy need the support of various social sciences including economics. But experiences in Indonesian development phase of 1966-98, showed that it has helped economic growth tremendously, but it also resulted in social injustices. And above all it ended with a serious multidimentional crisis in 1997. Because of that a new economics is proposed to replace the old American Neoclassical economics. This new economics should be founded on Indonesian economic history and culture through serious empirical-inductive method. This is not to reject completely Neoclassical Economics but to modify it in such way to become Indonesian Institutional Economics.Keywords: Peopleâs Economy, Economic History, Economics Teaching.